Systematic Characterization of the Group 2 House Dust Mite Allergen in Dermatophagoides microceras - Hu, Rei-Hsing; Wu, Chia-Ta; Wu, Ting-Shuan; Yu, Feng-Yih; Ko, Jiunn-Liang; Lue, Ko-Huang; Liu, Yu-Fan (Frontiers in Cellular and Infection Microbiology, 2022)
Background Allergic asthma, a chronic airway inflammatory disease, is a critical public health problem. Indoor house dust mites (HDMs) could cause allergic asthma. The prevalence of sensitization to Dermatophagoides microceras (Der m) was approximately 80% and is related to the immunoglobulin E crossing-reactivity of mites belonging to the same genus, Dermatophagoides pteronyssinus (Der p) and Dermatophagoides farina (Der f). However, studies on Der m are scant. Methods We used integrated OMICs approaches to identify and characterize the group 2 mite allergen-like protein in Der m (Der m 2). We established a Der m 2-induced allergic asthma mouse model and treated the mice with a fungal immunomodulatory protein (FIP-fve) isolated from Flammulina veluptipes to evaluate the allergenicity of Der m 2 and the immunomodulatory effects of FIP-fve. Results By performing de novo draft genome assembly and comparative genome analysis, we identified the putative 144-amino acid Der m 2 in silico and further confirmed its existence through liquid chromatography–tandem mass spectrometry. Der m 2 is a lipopolysaccharides (LPS)-binding protein. Thus, we examined the LPS-binding activity of recombinant Der m 2 by performing molecular docking analysis, co-immunoprecipitation (Co-IP), and a pull-down assay. Der m 2 elicited the production of pro-inflammatory cytokines, interleukin (IL)-6, and IL-8 in BEAS-2B cells, a human bronchial epithelial cell line, and induced airway hyperresponsiveness in mice. Furthermore, in mice sensitized with Der m 2, the administration of FIP-fve in either the earlier stage or the late stage, FIP-fve alleviated allergic asthma by moderating airway inflammation and remodeling. Conclusions Der m 2 induced inflammatory responses in cell and mouse models. FIP-fve alleviated inflammation in Der m 2-induced asthma in mice by exerting an immunomodulatory effect.